Penggunaan Tempat Sampah Bermotif Terhadap Perilaku Buang Sampah Pada Tempatnya di Sekolah Dasar Negeri Wilayah Argomulyo, Sedayu, Bantul - Rashid Purnomo; Lucky Herawati; Choirul Amri (Poltekkes Kemenkes Yogyakarta, 2017)
Waste is something which is not used anymore, disliked or discarded from human activities and is not produced by itself. In the study sites, i.e. State Elementary Schools of Panggang and Puluhan, which are located in Argomulyo, Sedayu, Bantul Regency, waste bins that are intended to sort the waste by printing the instruction on it, have been provided. But the instruction was not clear enough for the students. This study applied patterned waste bins to facilitate the students in sorting their wastes to the right places. The patterned bins utilized the existing ones by changing the appearance without reducing the function. There were three kinds of bins, i.e. separately for paper wastes, plastic and bottle wastes, and leaves and food wastes. The type of the study was a post-test only control group designed experiment. Panggang State Elementary School was appointed as the treatment group, meanwhile Puluhan State Elementary School was as the control. The data about the waste which were appropriately dumped into the right bins were observed daily after school for a month. The average of the observation then were analysed by using independent t-test at ? = 0,05; and the results show that the application ofpatterned bins influences students’ bahavior to throw their wastes in place. This conclusion is because of the instructions of the bins are easy to follow and the students were interested withthe pictures.